Akribeia certainty and ontology of mathematics in Alessandro Piccolomini's "De certitudine mathematicarum" - Campillo Bo, Álvaro José (History of metaphysics, 2025)
"This book provides a comprehensive study of the origins of seminal early modern debates on the certainty and ontology of mathematics. It analyzes Alessandro Piccolomini's De certitudine mathematicarum (1547), a work that ignited widespread controversy by challenging the scientific status of mathematics. The study delves into Piccolomini's logical doctrines, his philosophy of mathematics, and his perspectives on the relationship between mechanics and natural philosophy. Special attention is given to Piccolomini's ancient and medieval sources, the 16th-century rediscovery of Proclus' In Euclidem, and the influence of Priscian's In De Anima"--